2016
DOI: 10.1080/10615806.2016.1228900
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences moderate associations of coping strategies and posttraumatic stress disorder symptom clusters among women experiencing partner violence: a multigroup path analysis

Abstract: Background Past research underscores the key role of coping strategies in the development, maintenance, and exacerbation of posttraumatic stress disorder (PTSD) symptoms. The goal of the current study was to extend existing literature by examining whether race/ethnicity moderates the relations among coping strategies (social support, problem-solving, avoidance) and PTSD symptom clusters (intrusion, avoidance, numbing, arousal). Methods Participants were 369 community women (134 African Americans, 131 Latinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 97 publications
(130 reference statements)
2
26
1
Order By: Relevance
“…Several studies reveal that women with IPV experiences are more likely to report physical and emotional symptom of stress (Ziaei et al 2016;Wiess et al 2017). The results of Weiss et al (2017) study among women experiencing partner violence demonstrate that greater avoidance coping is related to more symptoms of PTSD in American women. Rashti and Golshokouh (2010) reported significant correlation between physicalpsychological and sexual violence with PTSD among married women.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies reveal that women with IPV experiences are more likely to report physical and emotional symptom of stress (Ziaei et al 2016;Wiess et al 2017). The results of Weiss et al (2017) study among women experiencing partner violence demonstrate that greater avoidance coping is related to more symptoms of PTSD in American women. Rashti and Golshokouh (2010) reported significant correlation between physicalpsychological and sexual violence with PTSD among married women.…”
Section: Discussionmentioning
confidence: 91%
“…In order to be more confident in the findings of this study, especially regarding limited studies on the role of spirituality in clinical setting and the spiritual needs of nursing students, more similar studies should be conducted. Given spirituality [58] and coping strategies [59] are to some extent dependent on ethnicity, the generalizations of the research findings to other ethnic groups should be carried out with caution and it is suggested that similar studies are conducted in other ethnic groups. This cross-sectional study was conducted to assess the factors predicting clinical clerkship satisfaction, it is suggested further studies utilized longitudinal method to assess these factors.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, research suggests that among Asian Americans the link between disengagement coping and distress may not be as strong as it is for White Americans (Chang, ). Other research has shown that the positive association between avoidance coping and PTSD is particularly strong for African American women, as compared with White and Latina women (Weiss et al, ).…”
Section: Introductionmentioning
confidence: 95%